Set free : a life-changing journey from banking to buddhism in bhutan - Slade, Emma. (Summersdale : United Kingdom, 2017)
In 1997, Emma Slade was taken hostage in a hotel room on a business trip to Jakarta. Over the ensuing months the trauma following the event took hold. Realising her view on life had profoundly changed she embarked upon a journey, discovering the healing power of yoga and, in Bhutan, opening her eyes to a kinder, more peaceful way of living.
Keywords: Slade, Emma -- Captivity -- 1997.; Slade, Emma -- Journey; Kidnapping -- Indonesia